Transcriptional Control of the Lateral-Flagellar Genes of Bradyrhizobium diazoefficiens - Mongiardini, Elias Javier (2017)
Bradyrhizobium diazoefficiens, a soybean N2-fixing symbiont, possesses a dual flagellar system comprising a constitutive subpolar flagellum and inducible lateral flagella. Here, we analyzed the genomic organization and biosynthetic regulation of the lateral-flagellar genes. We found that these genes are located in a single genomic cluster, organized in two monocistronic transcriptional units and three operons, one possibly containing an internal transcription start site. Among the monocistronic units is blr6846, homologous to the class IB master regulators of flagellum synthesis in Brucella melitensis and Ensifer meliloti and required for the expression of all the lateral-flagellar genes except lafA2, whose locus encodes a single lateral flagellin. We therefore named blr6846 lafR (lateral-flagellar regulator). Despite its similarity to two-component response regulators and its possession of a phosphorylatable Asp residue, lafR behaved as an orphan response regulator by not requiring phosphorylation at this site. Among the genes induced by lafR is flbTL, a class III regulator. We observed different requirements for FlbTL in the synthesis of each flagellin subunit. Although the accumulation of lafA1, but not lafA2, transcripts required FlbTL, the production of both flagellin polypeptides required FlbTL. Moreover, the regulation cascade of this lateral-flagellar regulon appeared to be not as strictly ordered as those found in other bacterial species.